Cardiac computed tomography in certified German chest pain units - Breuckmann, Frank; Hochadel, Matthias; Voigtländer, Thomas; Haude, Michael; Schmitt, Claus; Münzel, Thomas; Giannitsis, Evangelos; Mudra, Harald; Heusch, Gerd; Schumacher, Burghard; Barth, Sebastian; Schuler, Gerhard; et al. (Critical pathways in cardiology, 2016)
Objective:The German Cardiac Society runs a nation-wide certification campaign for specialized chest pain units (CPUs). So far, cardiac computed tomography (CT) is not an integral part of such certification. The aim of our study was to analyze whether or not cardiac CT is nevertheless routinely used